Estado de la investigación del uso de elementos biológicos en mampuestos y hormigón - Zárate Villacrés, Andrea Natali (2024)
ABSTRACT: The current construction system does not take into account the finite role of human resources, which is why there is widespread interest in recent years in developing more sustainable construction materials, including the use of fungal mycelium because these mycelium-based materials have potential properties for a wide range of construction applications. In the present work, existing research data on the composition of myceliumbased materials and the variables in their elaboration process are analyzed with the objective of making a proposal for their incorporation in Ecuador. The results showed that Pleurotus Ostreatus and Ganoderma Lucidum strains are the most common in the elaboration of these biocomposites, this is explained by their rapid rate of colonization of hyphae on the substrate, which reflects better mechanical properties. However, for the elaboration of mortars and concrete repair there is not a vast amount of research so it is largely unexplored.